The Need to Revive Islamic Philosophy - Muqtedar Khan, Mohammed A. (Intellectual Discourse, 2013)
This paper argues that the contemporary attempts at reviving Islamic civilization will remain incomplete until a simultaneous effort is made to revive Islamic philosophy. This paper identifies the characteristics of Islamic philosophy and underscores its significance to Islamic intellectual renaissance. Islamic philosophy has a unique dimension-it encompasses science and spirituality along with reason and logic. Arguing that perhaps the decline of philosophy was an important element in the decline of Islamic civilization, the paper contends that Muslim efforts at negotiating modernity or appropriating science will not be successful without the support of a rejuvenated Islamic philosophical tradition.